A transformation from Chalk and talk to Online learning- A new mantra for future (International Journal of Food and Nutritional Sciences, 2019)
Over the last two years, the educational landscape has shifted dramatically. The educationalsystem worldwide was also impacted by the Carona. The effects of Carona on elementary,secondary, and tertiary education have been devastating. The academic community'sadministrators, teachers, and students suffer from lost time, are unable to attend regularlyscheduled classes, and are unable to administer and take examinations.